Expression Analysis of Sound Vibration-Regulated Genes by Touch Treatment in Arabidopsis - Ghosh, Ritesh; Gururani, Mayank A.; Ponpandian, Lakshmi N.; Mishra, Ratnesh C.; Park, Soo-Chul; Jeong, Mi-Jeong; Bae, Hanhong (Frontiers in Plant Science, 2017)
Sound vibration (SV) is considered to be a mechanical stimulus which gives rise to various physiological and molecular changes in plants. Previously, we identified 17 SV-regulated genes (SRGs) which were up-regulated by SV treatments in Arabidopsis. Here, we analyzed the expression pattern of similar genes after an exposure of 500 Hertz at 80 decibels, for various time periods. Simultaneously, we confirmed the SV-mediated expression of these genes under lighted condition as many of them were reported to be dark-induced. For this, we designed an improved SV treatment chamber. Additionally, we checked the electrolyte leakage (EL), photosynthetic performance and expression of mechanosensitive (MS) ion channel genes after 5 days of SV treatment in the illuminated chamber. EL was higher, and the photosynthetic performance index was lower in the SV-treated plants compared to control. Seven out of the 13 MS ion channel genes were differentially expressed after the SV treatment. Simultaneously, we checked the touch-mediated expression pattern of 17 SRGs and 13 MS ion channel genes. The distinct expression pattern of 6 SRGs and 1 MS ion channel gene generate an idea that SV as a stimulus is different from touch. Developmental stage-specific expression profiling suggested that the majority of the SRGs were expressed spatiotemporally in different developmental stages of Arabidopsis, especially in imbibed seed, seedlings and leaves.